ANALISIS PENGARUH PENAMBAHAN DAUN JAGUNG PADA KERAMIK BERPORI BERBAHAN DASAR TANAH LEMPUNG - Ayu Amalya Rahma; Ety Jumiati; Ridwan Yusuf Lubis (Indonesian Physics Communication, 2023)
Corn leaves are agricultural waste that contains silica compounds and functions to reduce cracks in the drying of porous ceramics. Variations in the composition of clay and corn leaf ash are: 100% : 0%; 90% : 10%; 80% : 20%; and 70% : 30%. The manufacture of porous ceramics uses a dry pressing technique with a presure of 4 tons for 10 minutes, using a 3 × 3 × 3 cm3 mold, fired using a furnace at 900°C for 2 hours and allowed to cool for 24 hours. The characterization used namely density, porosity, water absorption, hardness and compressive strength. The result of the charaterization of porous ceramics is: density 1,20 – 1,79 g/cm3; porosity 29,75% – 61.03%; water absorption 16,6% – 50,8%; hardness 41,41 – 187,58 MPa; and compressive strength 3,51 – 84,49 MPa. The more addition of corn leaf ash caused an increase in porosity and to water absorption and decrease in density, hardness and compressive strength.